TV DOCUMENTARY PRODUCTION "THE EXISTENCE OF FAKE NUMBER PLATES" - Mutiah, Tuty; Andi Setyawan; Fajar Muharam; Adityo Fajar; Ken Norton Hutasoit; Bonardo Marulitua A (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research was conducted to find out more about how behind the making of fake plates and why people prefer to use fake number plate making services instead of making them from official institutions (samsat). This documentary film uses the field research method. Field Research is research conducted directly into the field in order to obtain complete and valid data. This research aims to find out the activities of buying and selling fake plates of motorised vehicle numbers in terms of Law Number 22 Year 2009 and Indonesian law in Tangerang City. In addition, it is also to find out the process of buying and selling vehicle number plates because the problem is that the object (Fake Motor Vehicle Number Plates) being traded can be detrimental to the buyer because there is article 68 in the Law of the Republic of Indonesia Number 22 of 2009 concerning road traffic and transportation which prohibits the use of these goods. Based on the results of documentary production, it is found that the reason people use the service of making paslu number plates is because the original plate is damaged, avoiding the police to get a ticket, and also the reason for avoiding bureaucracy related to Foreign Citizens (WNA).